Tourism language accommodation of Ubud-Bali: the virtual landscape linguistics (VLL) through google street view - Eka Dian Savitri; Kartika Nuswantara; Aurelius Ratu (Politeknik Negeri Bali, 2022)
This study reveals how Virtual Landscape Linguistics (VLL) in Ubud-Bali can describe the community’s attitude when facing the global tourism industry. Data in shop signboards, information boards, and building names were collected using documentation techniques through the Google Street View application (update 2019–2021) along Raya Ubud Street, Bali, Indonesia. The selected data represents the categories of language variation and monolingual-multilingual signs. The findings show that English is used in most commercial signage, both monolingual and multilingual outdoor signs. On the other hand, the local language is seen on monolingual and multilingual outdoor signs in traditional restaurants, information boards, and vernacular building names. Through the display of English signage, tourists worldwide can see that Ubud has provided complete accommodation needs for foreign tourists. In addition, tourists can also see that the use of local languages ​​such as Indonesian and Balinese on commercial signage and vernacular buildings shows the authentic value and culture of the local community as a tourist attraction. This study shows that VLL in the context of tourism has two functions. First, VLL helps travelers plan and organize their vacations better. Second, VLL allows stakeholders to promote their tourist areas virtually without neglecting their natural appearance.